Effect of indigenous AM fungi and BCAs on health of apple seedlings grown in replant disease soil - BHARAT, NARENDER K. (Indian Phytopathology, 2013)
The apple replant problem i.e. poor growth and short life of apple trees planted at sites where apple trees grew before, is wide spread and due to various abiotic and biotic stresses. These include harmful microorganisms and nutritional deficiencies or excesses, soil pH, phytotoxins etc. Due to its complex etiology, replant problem is very difficult to manage and only practice adopted worldwide for its management is soil fumigation with chemical fumigants. But soil fumigation with chemicals failed to provide a sustainable growth of newly planted seedlings as it also destroyed beneficial soil microflora including arbuscular-mycorrhizal fungi (AMF) and biocontrol agents (BCAs) besides other environmental issues. Hence, to develop a biologically sustainable approach to manage this problem in apple orchards, present pot culture experiment was conducted to see the effect of indigenous AM fungi and BCAs individually or in combinations on the growth of newly planted apple seedlings in apple replant diseased (ARD) soil with and without formaldehyde fumigation. The experiment showed that AMF plus BCA inoculation resulted in improvement in the growth of inoculated seedlings viz., seedling height, stem diameter, leaf area, seedling fresh and dry weights etc. than that of un-inoculated ones. The leaf nutrient status was also improved in inoculated seedlings. The Effect of inoculation of AM fungi and BCAs was more prominent w.r.t. growth improvement in the soil fumigated with formaldehyde.